Down a narrow road identity and masculinity in a Uyghur community in a Uyghur community in Xinjiang China - Dautcher, Jay 1963- (Harvard East Asian monographs, 2009)
This ethnography presents a thick description of life in the Uyghur suburbs of Yining, a city near the border with Kazakhstan, and situates that account in a broader examination of Uyghur culture. Its four sections explore topics ranging from family life to market trading, from informal socializing to forms of religious devotion. Uniting these topics are an emphasis on the role folklore and personal narrative play in helping individuals situate themselves in and create communities and social groups, and a focus on how men's concerns to advance themselves in an agonistic world of status competition shape social life in Uyghur communities.